Does Family Ownership Weaken Corporate Carbon Performance? - Septiany, Sheila; Jurnali, Teddy; Suparman, Meiliana; Wati, Erna; Intany, Neza (Jurnal ASET (Akuntansi Riset), 2026)
This study investigates whether family ownership affects carbon performance among publicly listed firms in Indonesia.  The study uses 451 firm-year observations from 2019–2023 from firms that consistently disclose sustainability information. Panel data regression was applied, and robustness is assessed using Coarsened Exact Matching (CEM).  The results show that family ownership has a negative and statistically significant effect on carbon performance, indicating that stronger family control is associated with weaker carbon performance and environmental accountability. This suggests that family-controlled firms prioritize internal stability and socioemotional considerations, which reduce incentives for transparent reporting and external scrutiny. However, some family firms may still achieve lower emissions through tighter internal monitoring despite limited disclosure quality.  These findings extend agency theory and socioemotional wealth theory by highlighting how ownership concentration shapes sustainability behavior in an emerging-market context. Practically, regulators and firms should strengthen board independence, enhance sustainability oversight, and encourage standardized carbon performance frameworks such as GRI 305 to improve transparency and credibility.  The novelty of this study lies in examining the under-researched relationship between family ownership and carbon performance in Indonesian listed firms, thereby enriching the corporate governance and sustainability literature.